Functional Mapping of the Cerebral Cortex Safe Surgery in Eloquent Brain - Byrne, Richard W. (Springer International Publishing : Imprint: Springer, 2016)
This book provides up-to-date, practical information on functional mapping in order to assist neurosurgeons responsible for safely removing lesions in and around eloquent cortex - one of the greatest challenges in neurosurgery.  The roles of pre- and intraoperative mapping techniques are clearly explained, highlighting the advantages and limitations of each tool available to the neurosurgeon. The inclusion of treatment algorithms for applications in specific clinical circumstances ensures that the book will serve as a clear guide to this most complex of neurosurgical problems. To further assist the reader, instructive clinical case examples, accompanied by intraoperative photos and other illustrative material, help to explain the applications of functional mapping of eloquent cortex in different pathologies. Practitioners will find the book to be a ready guide to navigation of the practical decisions commonly faced when operating in eloquent cortex.